Vaccination for Respiratory Syncytial Virus: A Narrative Review and Primer for Clinicians - Kay Choong See (Vaccines, 2023)
Respiratory syncytial virus (RSV) poses a significant burden on public health, causing lower respiratory tract infections in infants, young children, older adults, and immunocompromised individuals. Recent development and licensure of effective RSV vaccines provide a promising approach to lessening the associated morbidity and mortality of severe infections. This narrative review aims to empower clinicians with the necessary knowledge to make informed decisions regarding RSV vaccination, focusing on the prevention and control of RSV infections, especially among vulnerable populations. The paper explores the available RSV vaccines and existing evidence regarding their efficacy and safety in diverse populations. Synthesizing this information for clinicians can help the latter understand the benefits and considerations associated with RSV vaccination, contributing to improved patient care and public health outcomes.